More on official misconduct - Caiden, Gerald E.; Caiden, Naomi J. (1995)
"Taking a global view, spanning different continents, of the incidence of unethicality and its level, the authors analyse its various symptoms. They then analyse the political, economic and social impacts of corruption, and discuss various international remedial initiatives taken in the private/public sectors at institutional level to show how the fight against the malady is proceeding"
Keywords: Misconduct in office - India; Public administration - India; Administrative responsibility - India; Civil service